INVESTIGATING THE LONG-TERM EFFECTS OF DIFFERENT DIETARY PATTERNS ON CARDIOVASCULAR HEALTH - Naif Gazan Nashi Alotaibi, Abdullah Ali Aldhafyan, Jeza Mahdi Zaiyed Alotaibi, Naif Gazan Nashi Alotaibi, Sarah Jahaz Faleh Alharthi, Saad Abdulrahman Saad Alsaadi, Dalal Ayeadh Aweadh Alzeadi, Mubarak Naser Mubarak Alrokan, Hatim Saad Jazaa Almutairi, ,; Haya Fahad Abdullah Al Thani, Haya Saad Naser Albeshi, Abrar Abdul Rhman Alharbi, Awatif Hamoud Alsolmi, Ahmed Hamed Mohammed Alnowmasi, Hussain Ibrahim Hussain Dhayihi, (Chelonian Research Foundation, 2022)
The correlation between dietary patterns and cardiovascular disease has been extensively studied. However, it is crucial to evaluate the interrelationship between the nutritional makeup of foods and the identification of healthy dietary patterns while doing research in this area. This paper examines the difficulties associated with studying food trends and their relevance to public health campaigns. Several statistical techniques have been developed to analyze dietary patterns using data on the eating habits of a community. The assumptions behind food categorization have some limits. However, this study has the ability to consistently identify foods and dietary patterns that have a favorable correlation with health. The continual development of food composition databases is closely related to this activity. However, it has some limits, such as the challenge of staying up to date with changes in foods and newly discovered components, as well as the need to sample foods and keep up with advancements in chemical analysis procedures. Ultimately, dietary patterns serve as the foundation for existing dietary standards and public health initiatives. However, the research challenges that arise, such as the categorization of food and the impact of different cuisines on dietary patterns, may also be applicable in these contexts. The investigation of dietary patterns in the prevention of cardiovascular disease is faced with many methodological obstacles with the formation of food groups and the constraints of food composition databases. In addition, there are additional factors to consider about the environmental consequences of suggested food habits. Future research should focus on developing more precise approaches in many analytical domains across the full knowledge chain. Keywords: Dietary supplement, healthy nutrition, cardiovascular disease, review.